Application d’une sonde radicalaire aux études des macromolécules, des cristaux plastiques et des cristaux liquides - Rudolf Lenk (CHIMIA)
The piperidin free radicals, detected by means of E.S.R. spectroscopy or Electron-Nuclear Double Resonance seem to be quite adequate as a free radical probe for the investigation of modern organic systems such as macromolecules, plastic crystals and liquid crystals :